2023
DOI: 10.3390/ijerph20031928
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parabens and Bisphenol A Concentration Levels in Wild Bat Guano Samples

Abstract: Parabens and bisphenol A are synthetic compounds found in many everyday objects, including bottles, food containers, personal care products, cosmetics and medicines. These substances may penetrate the environment and living organisms, on which they have a negative impact. Till now, numerous studies have described parabens and BPA in humans, but knowledge about terrestrial wild mammals’ exposure to these compounds is very limited. Therefore, during this study, the most common concentration levels of BPA and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The only previous work on parabens in wild animals in Poland concerns studies on wild bat guano [ 29 ], in which MeP, EtP, PrP and BuP have been found (Table S2 in the S1 File ). This observation together with results obtained in present investigation and studies on parabens in the elements of the natural environment [ 56 , 57 ] have indicated that environment in Poland is polluted with parabens to a relatively considerable extent , what may translate to the risk of exposure to these substances not only in humans [ 17 , 58 ] and domestic animals [ 22 ], but also in wild animals [ 29 ]. Moreover, the presence of parabens in the wild boar hair may be connected with the lifestyle of this animal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only previous work on parabens in wild animals in Poland concerns studies on wild bat guano [ 29 ], in which MeP, EtP, PrP and BuP have been found (Table S2 in the S1 File ). This observation together with results obtained in present investigation and studies on parabens in the elements of the natural environment [ 56 , 57 ] have indicated that environment in Poland is polluted with parabens to a relatively considerable extent , what may translate to the risk of exposure to these substances not only in humans [ 17 , 58 ] and domestic animals [ 22 ], but also in wild animals [ 29 ]. Moreover, the presence of parabens in the wild boar hair may be connected with the lifestyle of this animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Only single studies concern the biomonitoring of parabens in wild terrestrial mammals. According to the best knowledge of the authors there are only three such studies describes parabens in the liver of the polar bear [ 27 ], liver and kidney of the black bear [ 28 ] and bat guano [ 29 ]. Moreover, two mentioned above studies on the bears have been conducted on a very limited number of samples (not exceeding ten) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that bats are highly exposed to various environmental pollutants, including e.g. heavy metals, organochlorine contaminants, parabens and pesticides, and bat guano is an appropriate matrix for such studies [71][72][73].…”
Section: Plos Onementioning
confidence: 99%
“…blood, urine, tissues, hair), that require animals to be captured or killed, feces samples may be gathered without significantly interfering with animal's life. Moreover, previous studies have indicated that bat guano may be an appropriate matrix to study the exposure of this animal group to various substances polluting the natural environment, such as parabens, pesticides and heavy metals [71][72][73]. Undoubtedly guano analysis also has its drawbacks such as impossibility to assign samples to certain animals, and therefore the animal's age, sex, and health status cannot be determined, and these parameters often affect the degree of exposure to environmental pollutants [98,99].…”
Section: Plos Onementioning
confidence: 99%